Improvement of AC Bus Voltage Stability with Current Control Inverter - Nugroho, Bayu Rahmad; Maulidin, Reza; Kusmantoro, Adhi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2025)
This research focuses on the development and analysis of a current control method for inverters, which demonstrates superior performance compared to the more conventional voltage control method. Current control in inverters offers several significant advantages, including faster dynamic response, constant switching frequency, and the ability to effectively reduce harmonic distortion, which is often a challenge in modern power systems. Additionally, this method is capable of maintaining system stability even when it had complex load variations and fluctuating operating conditions. In this study, we implement a fuzzy logic approach to simulate current control in an inverter integrated with a photovoltaic (PV) renewable energy system. The simulation results indicate that the proposed current control method not only enhances overall energy efficiency, but also extends the operating range of the inverter, allowing the system to operate optimally under various load conditions.